Price discrimination in informal labor markets in Bogotá: an audit experiment during the 2018 FIFA World Cup - Paula Zamora; César Mantilla; Mariana Blanco (Journal for Labour Market Research, 2021)
We conducted an audit experiment to examine whether street vendors in Bogotá (Colombia) exert price discrimination based on buyers' attributes, such as gender and nationality, and based on product characteristics, such as the increasing marginal valuation of items needed to complete a collection. We exploited the seasonal demand for album stickers related to the FIFA World Cup Russia 2018. In our within-subjects design, experimenters carried out in-person audits and quoted a pre-determined list of missing stickers. They interacted with 59 sticker vendors located in five geographic clusters and collected 287 vendor-buyer interactions. We find that prices quoted to foreign buyers are higher than prices quoted to Colombian buyers. By contrast, we do neither find evidence supporting direct genderbased discrimination, nor that vendors charge a higher price per sticker when the list of missing stickers is shorter. We complement the study with a qualitative analysis based on interviews that reveal vendors' pricing strategies, their awareness of price discrimination, and the trade of counterfeits. The qualitative results suggest that price discrimination appears to be unconscious.
Keywords: C93; J46; 330; Colombia; Dual labor markets; Football; Latin america; Sports; Street vendors